Evaluación del efecto de la temperatura en el proceso fermentativo en la producción de cerveza artesanal tipo Blonde Ale (2021)
The project focused on the analysis of the temperature in the fermentation stage. For its development, the production of a blonde ale type ale was defined, 280 L of must was prepared based on three types of malt, Pilsen, caramunnich II and carapils; two types of hops, cascade and bravo, and a yeast of the genus Saccharomyces Cerevisiae Safeale US-05 as a fermenting microorganism. The must was characterized with a density of 1,049 g / ml, pH of 5.26 and 13.9 ° brix, and it was fermented for 7 days, evaluating two simultaneous cases: in the first case, the fermentation was carried out non-isothermally (variable temperature) (F1) and in the second (F2) the fermentation temperature (isothermal process) was controlled at 18 ° C. Both cases were compared by measuring variables such as substrate consumption, ethanol formation, growth and behavior of biomass concentration, some kinetic parameters in the fermentation stage, and physicochemical, microbiological and sensory analyzes of the final product were carried out.